Griscelli Syndrome: A Case Report - MANSOURI NEJAD, Seyed Ebrahim; YAZDAN PANAH, Mohammad Javad; TAYYEBI MEIBODI, Naser; ASHRAFZADEH*, Farah; BEIRAGHI TOOSI, Mehran; AKHONDIAN, Javad; ESLAMIEH, Hossein (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Mansouri Nejad SE, Yazdan panah MJ, Tayyebi Meibodi N, Ashrafzadeh F, Akhondian J, Beiraghi Toosi M, Eslamieh H. Griscelli Syndrome: A Case Report. Iran J Child Neurol. 2014 Autumn;8(4): 72-75. Objective Griscelli syndrome (GS) is a rare autosomal recessive immune deficiency disorder that presents with pigmentary dilution of the skin and hair, recurrent skin and pulmonary infections, neurologic problems, hypogammaglobulinemia, and variable cellular immunodeficiency. Three mutations have been described in different phenotypes of the disease. In most of cases, GS leads to death in the first decade of life. In this article, we report a one-year-old child with type 2 GS who suffers from pigmentation disorder and hypogammaglobulinemia. References Kharkar V, Pande S, Mahajan S, Dwiwedi R, Khopkar U. Griscelli syndrome: a new phenotype with circumscribed pigment loss? Dermatol Online J 2007 1;13(2):17. Sheela SR, Latha M, Susy JI. Griscelli syndrome: Rab 27a mutation. Indian Pediatrics 2004; 41:944-947. González Carretero P, Noguera Julian A, Ricart Campos S, Fortuny Guasch C, Martorell Sampol L. Griscelli-Prunieras syndrome: report of two cases. An Pediatr (Barc) 2009 ; 70(2):164-7. Szczawinska-Poplonyk A, Kycler Z, Breborowicz A, Klaudel-Dreszler M, Pac M, Zegadlo-Mylik M, et al. Pulmonary lymphomatoid granulomatosis in Griscelli syndrome type 2. Viral Immunol 2011 Dec;24(6):471-3. Durmaz A, Ozkinay F, Onay H, Tombuloglu M, Atay A, Gursel O, et al. Molecular analysis and clinical findings of Griscelli syndrome patients. J Pediatr Hematol Oncol 2012 Oct;34(7):541-4. Reddy RR, Babu BM, Venkateshwaramma B, Hymavathi Ch. Silvery hair syndrome in two cousins: Chediak-Higashi syndrome vs Griscelli syndrome, with rare associations. Int J Trichology 2011; 3(2):107-11. Sahana M, Sacchidanand S, Hiremagalore R, Asha G. Silvery grey hair: clue to diagnose immunodeficiency. Int J Trichology 2012;4(2):83-5. Mahalingashetti PB, Krishnappa MH, Kalyan PS, Subramanian RA, Padhy S. Griscelli syndrome: hemophagocytic lymphohistiocytosis with silvery hair. J Lab Physicians 2012 Jul;4(2):129-30. Schuster F, Stachel DK, Schmid I, Baumeister FA, Graubner UB, Weiss M, et al. Griscelli syndrome: report of the first peripheral blood stem cell transplant and the role of mutations in the RAB27A gene as an indication for BMT. Bone Marrow Transplant 2001; 28:409-12. Shamsian BS, Nikoufar M, Esfahani SA, Shamshiri AR, Arzanian MT, Alavi S, et al. A 10-year single center survey of pediatric patients with histiocytic disorders in Iran. Turk J Pediatr 2011; 53(1):34-42.